Pengaruh Keterampilan Mengajar Guru terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Terpadu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to determine the effect of teacher teaching skills on student learning outcomes in integrated social studies subjects at SMP Negeri 4 Batuda'a Pantai, Gorontalo Regency. The research approach used in this study is a Quantitative approach using Descriptive research method The results showed that there was a Positive (5.376 > 2.004) and Significant (0.000 < 0.005) Influence between Teacher Teaching Skills on Student Learning Outcomes in Integrated Social Studies Subjects at SMP Negeri 4 Batuda'a Pantai Gorontalo Regency. The coefficient of determination from the previously obtained regression model is 0.344, this value means that 34.4% of the variability in student learning outcomes can be explained by the teaching skills of teachers in integrated social studies subjects at SMP Negeri 4 Batuda'a Pantai. In other words, the better the teacher's skills in managing the learning process, such as explaining material, guiding discussions, providing reinforcement, and managing the class, the higher the possibility of students achieving optimal learning outcomes.